Guide to RIBA Professional Services Contracts 2018 - Davies, Ian (Architect) (RIBA Publishing, 2018)
The 2018 edition of this guide explains how to use, understand and get the most out of the RIBA Professional Services Contracts, which have been updated from the RIBA Agreements 2010 (and 2012 revision). With guidance on how to choose, prepare and complete the right contract, it is an essential companion for anyone using these industry-standard forms. The guide is written for architects and consultants to help practitioners develop a greater understanding of the role and responsibility of each party to the agreement.